2015
DOI: 10.1007/8904_2015_461
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Improves Clinical Outcome of Patients Affected by Glycogen Storage Disease Type Ib

Abstract: Frequency (1.5 ± 0.1 vs. 6.0 ± 0.6, p = 0.003) and severity of infections (2.2 ± 0.2 vs. 3.7 ± 0.4, p = 0.003) were lower and mean value of neutrophil count (1,583 ± 668 vs. 941 ± 809, p = 0.03) higher during vitamin E supplementation. Neutrophil function results improved during vitamin supplementation. PCDAI showed a significant reduction in the inflammatory activity during vitamin E supplementation (9 ± 1.4 vs. 13 ± 1.2, p = 0.006). In seven patients G-CSF requirement decreased and the dose was reduced after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…Therefore, a starting dose of 2.5 micrograms/kg/day is recommended, and the lowest dose that controls infections should be used [33]. Supplementation with high dose vitamin E appears to boost the neutrophil count and improve function in GSD Ib, and supplementation may allow lower GCSF doses to be used [34]. Non-absorbable salicylates (Pentasa, Asacol, and Lialda) are the first line therapies for GSD enterocolitis.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a starting dose of 2.5 micrograms/kg/day is recommended, and the lowest dose that controls infections should be used [33]. Supplementation with high dose vitamin E appears to boost the neutrophil count and improve function in GSD Ib, and supplementation may allow lower GCSF doses to be used [34]. Non-absorbable salicylates (Pentasa, Asacol, and Lialda) are the first line therapies for GSD enterocolitis.…”
Section: Treatmentmentioning
confidence: 99%
“…Non-absorbable salicylates (Pentasa, Asacol, and Lialda) are the first line therapies for GSD enterocolitis. Steroids and immunomodulators must be used with caution due to the metabolic consequences and associated immune dysfunction [34].…”
Section: Treatmentmentioning
confidence: 99%
“…It has been suggested that vitamin E also has a role in improving neutrophil count and reducing the frequency and severity of infections, and its effectiveness in reducing the frequency of infection and improving neutropenia has been reported in GSD 1b patients (28) . Although it is easy to argue that vitamin E supplementation would have many advantages over the use of G-CSF, in terms of route of administration (oral vs subcutaneous, respectively) and safety/adverse effects, its use as a strategy to reduce or avoid G-CSF has not been systematically studied, and the current evidence is considered insufficient to recommend routine use of vitamin E supplementation alone as a G-CSF sparring strategy.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Vitamin E supplementation aimed at lowering oxygen radicals has been found to increase circulating neutrophil numbers and improve clinical outcome. 18 More recently, Veiga-da-Cunha et al showed that failure to eliminate a phosphorylated nonclassical glucose analog (1,5AG6P) is causing inhibition of glycolysis, and treatment with a 1,5-anhydroglucitol-lowering drug successfully treated neutropenia in the murine model of GSD Ib. 19 G-CSF use in the GSD Ib population has been life sustaining, but it is now apparent that it is not treating the underlying disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that bone marrow production of cells is normal, but apoptosis is occurring in the neutrophils resulting in premature death and neutropenia . Vitamin E supplementation aimed at lowering oxygen radicals has been found to increase circulating neutrophil numbers and improve clinical outcome . More recently, Veiga‐da‐Cunha et al showed that failure to eliminate a phosphorylated nonclassical glucose analog (1,5AG6P) is causing inhibition of glycolysis, and treatment with a 1,5‐anhydroglucitol‐lowering drug successfully treated neutropenia in the murine model of GSD Ib …”
Section: Discussionmentioning
confidence: 99%